New Federalism - McCrae, Stewart, 1919-2008 (1976)
"Canberra - The West Australian Premier (Sir Charles Court) has accused the Federal Liberal Government of filching State powers"--Newspaper clipping above image.
Title from caption list.
Part of the collection: Lindsay Foyle collection of cartoons, 1924-2016.
Inscriptions: "McCrae"--Artist's signature lower right
Condition: Spotting, stained, soiled, tears and yellowing.
Keywords: Court, Charles, -- Sir, -- 1911-2007 -- Caricatures and cartoons; Premiers -- Western Australia -- Caricatures and cartoons; Politicians -- Western Australia -- Caricatures and cartoons; Australian wit and humor -- Pictorial works; Australia -- Politics and government -- 1976-1990 -- Caricatures and cartoons